Should Liberal Democracy Respect Group Rights that Discriminate against Women and Apostates? - Cohen-Almagor, Raphael (Public Governance, Administration and Finances Law Review, 2023)
The paper examines the limits of state interference in proscribing cultural norms by considering gender discrimination, right of people to leave their community free of penalties, denying women appropriate education, and forced or arranged marriages for girls and young women. The discussion opens by reflecting on the discriminatory practices of the Pueblo tribes against their women and analysing an American court case, Santa Clara v. Martinez. It is argued that the severity of rights violations within the minority group, the insufficient dispute-resolution-mechanisms, and the inability of individuals to leave the community if they so desire without penalty justify state intervention to uphold the dissenters’ basic rights. Next, a Canadian case, Hofer v. Hofer, illustrates the problematics of denying reasonable exit right to members who may wish to leave their community. Subsequently, the discussion turns to the issue of arranged and forced marriages of girls and young women. While the latter is coercive the former is not. While forced marriages should be denounced as unjust, arranged marriages can be accepted. Finally, the paper considers denying education to women, arguing that such a denial is unjust and discriminatory.